Out in the field: examining the role of school-based experiences in preparing primary pre-service teachers as confident and competent teachers of science. Issue 2 (22nd January 2020) - Fitzgerald, Angela
ABSTRACT: At a basic level, it makes sense to involve pre-service teachers in school-based experiences (SBE) as a way of preparing them for the teaching profession. Little is known, however, about how SBEs might prepare pre-service teachers as future teachers of particular learning areas. The purpose of this study was to explore the impacts and highlight the implications of school-based experiences on primary pre-service teachers' confidence and competence in relation to the learning and teaching of science. Detailed questionnaires were completed by 146 primary pre-service teachers enrolled in a science education curriculum and pedagogy unit. In making further sense of this snapshot, 18 pre-service teachers participated in focus group interviews to share their insights. Key findings revealed that SBEs have an important role to play in breaking down barriers to the formation of a science learner/teacher identity and provide a lived experience of science learning/teaching that is ultimately critical in empowering primary pre-service teachers to teach science. Overall this project clarified the value of incorporating SBE into teacher education, particularly in relation to the learning area of science, but raised questions about this approach could be innovated to ensure equity and accessibility for pre-service teachers regardless of mode of study.